Correlation between Erection Hardness Score and Nocturnal Penile Tumescence Measurement. (12th June 2014) - Matsuda, Yohei; Hisasue, Shin‐ichi; Kumamoto, Yoshiaki; Kobayashi, Ko; Hashimoto, Kohei; Sato, Yoshikazu; Masumori, Naoya
Abstract Introduction The Erection Hardness Score (EHS) and the Sexual Health Inventory for men (SHIM) are patient‐reported outcome scoring systems for erectile function. It is unclear which is more reliable for predicting the objective erectile function. Aim The aim of this study was to evaluate whether the EHS could predict objective erectile function by measuring the maximal penile circumferential change (MPCC) with an erectometer. Methods The study included 98 patients who visited our clinic from 2005 to 2010. The erectile function was evaluated using the SHIM, EHS, and MPCC. The MPCC was measured with the largest circumferential change of three consecutive occurrences of nocturnal penile tumescence (NPT) determined using the erectometer. Main Outcome Measures We defined erectile dysfunction (ED) as MPCC < 20 mm and carried out multivariate analysis using logistic regression analysis to clarify the predictors for ED, with the variables including age, the SHIM score, and the EHS. We compared the tendency for MPCC ≥ 20 mm when EHS was 3 or more with that when EHS was 2 or less. Results The median age of the patients was 59.5 years (range 18–83). In logistic regression analysis, the EHS was the only predictor for ED with MPCC < 20 mm. The mean EHS in the MPCC < 20 mm group was 1.64 ± 0.20 (mean ± SEM) and that in the MPCC ≥ 20 mm group was 2.46 ± 0.13 (P = 0.0018). There was a correlation between the EHS and the MPCC (correlation coefficient = 0.33). In comparison with the group having an EHS of 2 or less, that with an EHS of 3 or more tended to have MPCC ≥ 20 mm (P = 0.013). Conclusions The EHS was correlated with the MPCC. The EHS represents the objective erectile function shown by the measurement of NPT. Matsuda Y, Hisasue S, Kumamoto Y, Kobayashi K, Hashimoto K, Sato Y, and Masumori N. Correlation between Erection Hardness Score and Nocturnal Penile Tumescence Measurement. J Sex Med 2014;11:2272–2276.